2023
DOI: 10.3390/healthcare11060885
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Social Features of Patients with Eye Injuries Admitted to a Tertiary Hospital: A Five-Year Retrospective Study from Crete, Greece

Abstract: Eye injuries are a major cause of visual disability worldwide and may present a burden to both quality of life of the sufferers and healthcare services. The aim of this study was to extract and triangulate information on the demographic, clinical, and social features of eye-injured adult patients admitted to a tertiary hospital in Greece. The design was a five-year retrospective study of eye-injured adult patients, admitted to the General University Hospital of Heraklion, Crete (GUHH), the single tertiary refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(52 reference statements)
1
1
0
Order By: Relevance
“…In our study, the majority of eye injuries (48.7 %) occurred during work-related activities, predominantly among men. This trend aligns with recent findings in a retrospective study conducted in Crete, Greece, where work-related eye injuries accounted for 60.9 % of cases [15]. What is concerning is that a significant proportion of patients with work-related eye injuries did not wear protective eyewear (85.6 %), even in high-risk activities where its use should be obligatory.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study, the majority of eye injuries (48.7 %) occurred during work-related activities, predominantly among men. This trend aligns with recent findings in a retrospective study conducted in Crete, Greece, where work-related eye injuries accounted for 60.9 % of cases [15]. What is concerning is that a significant proportion of patients with work-related eye injuries did not wear protective eyewear (85.6 %), even in high-risk activities where its use should be obligatory.…”
Section: Discussionsupporting
confidence: 88%
“…This problem extends beyond our country, as studies conducted in Asia and Australia have reported similarly high rates of noncompliance with protective eyewear among individuals with work-related ocular trauma [16], with some studies reporting even more alarming figures [13,17]. Kyriakaki et al reported that 90.5 % of their retrospective cohort did not wear protective eyewear in work-related eye injuries [15]. It is worth emphasising that a significant number of these eye injuries could have been prevented or avoided if protective eyewear were used.…”
Section: Discussionmentioning
confidence: 90%